Ground Proximity Warning System- GPWS - Davor Franjković; Tino Bucak; Nikica Hoti (Promet - Traffic&Transportation, 1970)
In this article the technical description of the Ground ProximityWaming System (GPWS) is presented in order to considersome of the flying safety factors in commercial aviation,as well as the aspects of interaction between the pilot and thesystem itself during the flight. Since it has been confirmed inpractice that the installation and utilisation of GPWS in aircraftsignificantly reduces the hazards caused by the ControlledFlight Into Ten·ain (CFIT) further development of GPWSequipment presents one of the most important steps in preventingthe ultimate consequences of such aircraft disasters.